ANALISIS SEMIOTIKA FILM MY STUPID BOSS - Resmardi, Rhicard Yulio; Siswanta, Dian Esti Nurati, (Solidaritas, 2017)
ANALISIS SEMIOTIKA FILM MY STUPID BOSSÂ Oleh:Rhicard Yulio ResmardiDian Esti NuratiSiswantaÂ ABSTRACTÂ This research was the excavation of the meaning of the message contained in a few selected scene in the movie